WEARABLE ACTIVITY TRACKERS AND OLDER ADULTS: IMPROVING HEALTH AND INDEPENDENCE. (11th November 2018) - Bowen, M; Cotten, S R; Peng, W; Kononova, A; Rikard, R
Abstract: Many older adults develop chronic diseases which correlate with low levels of activity. Chronic diseases result in decreased quality of life and premature mortality. Most older adults spend too much time in a sedentary state, despite evidence that 30 minutes of activity a day helps improve health. We interviewed 20 older adults from across the U.S. who had used a wearable activity tracker (WAT) for six months or longer. Users reported that WATs helped them lose weight, increase energy, and feel less pain. Users reported "doing what [they] want, " such as joining the grandkids on walks and being independent (e.g., no longer needing a cane due to increased strength). They reported lower resting heart rates and cholesterol, reducing the need for medication. Because of WATs, users were able to increase activity, improve health, and reduce the risk of premature mortality, allowing them to enjoy life with less pain and medication.